Analysis of the Relationship Between Somatic Diseases and Dentofacial Abnormalities and Deformities in Children - G. A., Ikramov; B. A., Khalmanov; А. И., Омонов; Н. Х., Бобоназаров (American Journal of Biomedicine and Pharmacy, 2026)
801 patients under 18 years of age diagnosed with dental anomalies and deformities were studied based on medical records, anamnesis and complaints of children. The study presents an analysis of the somatic diseases experienced by these children, dental diseases, including changes in the oral mucosa.